Peroxide penetration from the pulp chamber to the external root surface after internal bleaching - Palo, Renato Miotto [UNESP]; Valera, Marcia Carneiro [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Cardoso, Paula Elaine [UNESP]; Mancini, Maria Nadir Gasparoto [UNESP]; Pameijer, Cornelis H. (My University, 2010)
Purpose: To quantify the amount of peroxide penetration from the pulp chamber to the external surface of teeth during the walking bleaching technique. Methods: Seventy-two bovine lateral incisors were randomly divided over five experimental groups and one control (n= 12 per group): (1) 35% hydrogen peroxide (HP); (2) 35% carbamide peroxide (CP); (3) sodium perborate (SP); (4) (HP+SP); (5) (CP+SP) and (6) Control (CG), deionized water. All groups were treated according to the walking bleach technique. After 7 days at 37°C in an acetate buffer solution, 100 μl violet leukocrystal coloring and 50 μl peroxidase was added, producing a blue stain that could be measured in a spectrophotometer and then converted into peroxide μg/ml. Results: G5 exhibited the greatest penetration, while G2 and G3 produced the lowest values. All bleaching agents penetrated from the pulp chamber to the external root surface. There was a direct correlation between the presence of oxidative agents and penetration potential. Sodium perborate in distilled water was less oxidative and appeared to be the least aggressive bleaching agent.